Austrian business cycle theory: are 100 percent reserves sufficient to prevent a business cycle? - Bagus, Philipp Bagus (REVISTA PROCESOS DE MERCADO, 2012)
Economists in the tradition of the Austrian school have shown that one type of maturity mismatching can cause maladjustments and business cycles.1 When banks expand credit, by granting loans and creating demand deposits, they generate immediately withdrawable liabilities to finance longer-term loans. The newly created demand deposits do not represent a reduction of consumption, i.e., that characterized by real savings. As a con sequence, in terest rates are artificially reduced under the level they would have been in a free market reflecting real savings and time preference rates.2 Thus, entrepreneurs are prone to engage in more and longer projects than could be financed with the available supply of real savings. Before all projects that are financed by the credit expansion are finished, a bust occurs. An absence of realsavings to sustain the factors of production in the production pro cesses and to produce complementary and necessary capital goods becomes evident. As a result, malinvestments are liquidated and the structure of production is brought in line with consumer preferences again. This is the Austrian Business Cycle Theory (ABCT) in a nutshell. As a remedy Austrian economists such as Selgin (1988) and White (1999) have argued that a free banking system would be a means to inhibit the excessive credit expansion that causes business cycles. They maintain that the competition between banks would limit the credit expansion of the banking system effectively. Other Austrians such as Rothbard (1991) and Huerta de Soto (2006) have gone further and advocate a 100 percent re - rerve banking system ruling out credit expansion altogether.3 In this article it is argued that a 100 percent reserve system can still bring about artificial booms by maturity mismatching if there is a central bank or government support and guarantees for the ban king system. Even if we accept the case for a 100 percent re - serve requirement, we see that the maturity mismatching of liabilities and assets (borrowing short and lending long) is itself perilous–and in the same sense that fractional reserves are perilous.